Response of European carrot (Daucus carota) to different irrigation schedules and sowing methods under the mid-hill conditions of north-western Himalayas, India - PRIKXIT; SHARMA, J C; KLATE, AKANKSHA; SHARMA, ARCHANA (The Indian Journal of Agricultural Sciences, 2025)
Optimum irrigation scheduling and right sowing method are two main limiting factors for ensuring crop yield and is determined based on the information of yield attributing characters. The study was carried out during 2021–22 and 2022–23 at Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to determine precise irrigation schedule along with appropriate method of sowing in carrot (Daucus carota L.) for sandy loam soil of mid hills of north-western Himalayas. Two sowing methods (S1, Flat-bed and S2, Ridge) and four irrigation schedules, viz. I1 (IW/CPE 0.6); I2 (IW/CPE 0.8); I3 (IW/CPE 1.0) and I4 (IW/CPE 1.2) at 3 cm depth of irrigation were evaluated and replicated thrice in factorial randomised block design (F-RBD). Results of the study revealed that an increase in the irrigation frequency [IW/CPE 1.2 (I4)] resulted in significant increase in plant height (30.50%), root length (33.86%), root diameter (41.79%), root:shoot ratio (36.51%), net and gross root weight (75.77 and 58.43%) and carotene content (5.71%) compared to IW/CPE 0.6 irrigation schedule. Irrigation at IW/CPE 1.2 (I4) in ridge method of planting resulted in maximum total NPK uptake (92.40, 24.86 and 53.58 kg/ha), dry matter content (10.05%), yield (342.2 q/ha), net returns (₹ 5,22,892) and benefit:cost ratio (3.23). Hence, irrigation schedule at IW/CPE 1.2 with ridge method of sowing was proved to be the most effective approach to enhance yield, economics and efficient management of water resources.